Development Strategy of Kawatuna Landfill Management in Palu City - Muhammad Iqbal Rajaguni; Bagyo Yanuwiadi; Amin Setyo Leksono (The Indonesian Green Technology Journal, 2018)
Kawatuna landfill serves the end processing of waste in Palu city region.  Kawatuna landfill has actually been completed with various facilities like liquor processing, compost processing, and biogas catch, but its implementation is still like an open dumping. This research aims to set out a development strategy of Kawatuna landfill in Palu city.  This was a descriptive qualitative method by comparing Kepanjen Edu-tourism landfill in Malang district and Kawatuna landfill in Palu city.  This research focuses on the assessment parameter of sustainable solid waste management in a developing country.  Data were collected through observation, documentation, and interview.  The data of the research result of Kepanjeng Edu-tourism landfill and Kawatuna landfill management was then compared to determine its management gap, be analyzed, and be served as a material to develop a strategy of Kawatuna landfill development.   Development strategy of Kawatuna landfill is as follows (a) operational technique aspect with the fulfillment of all feasibility standards; (b) legality aspect with the elaboration of regulation technique of waste management; (c) institutional aspect by separating the role of regulatory and operator institution, SOP and SPM (Standar Pelayanan Minimal or Minimum Service Standards) setting, as well as coordination strengthening among stakeholders; (d) financing and economics aspect by optimizing APBN (State Budget) and APBD (Local Budget) Provincial/District/City Government, finance source development form external party and retribution; (e) health and environmental aspect by providing health insurance for community and environment around the landfill; and (f) social aspect by empowering society around the landfill.Keywords: Development, Landfill, Sustainable, Strategy, Waste